Education and Audiovisual Media: A Systemic Reflection for its Implementation, Strengthening and Sustainability - Marino-Jiménez, Mauro (2020)
The implementation of educational proposals, supported by the use of audiovisual media (AM) is abundant. However, beyond the development of good practices, it appears a complex process of production, functionality and sustainability, which ends up defining its long-term success or failure. On the other hand, conditions such as knowledge of the audiovisual narrative, the definition of product problems and the correct identification of the public, shows the confrontation with a reality that compromises reflection and analysis at different levels. In this sense, the present work develops a reflection on this field in three directions: bibliographic, disciplinary and systemic; with the intention of conceiving, respectively, the best educational practices sustained in the use of MA; greater impact on the community of the educational center itself; and provision of strategies to shape mutual understanding, which provides for the sustainability of its own production.